Click-chemistry approaches to π-conjugated polymers for organic electronics applications. Issue 10 (13th July 2016) - Marrocchi, Assunta; Facchetti, Antonio; Lanari, Daniela; Santoro, Stefano; Vaccaro, Luigi
Abstract : A survey of papers exploring the scope of click chemistry in the area of π-conjugated polymers for organic electronics is given. Abstract : Given the wide utility of click-chemistry reactions for the preparation of simple moieties within large architecturally complex materials, this minireview article aims at surveying papers exploring their scope in the area of π-conjugated polymers for application in organic electronics to enable advanced functional properties.